2022
DOI: 10.3390/ijerph192316048
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk, Income Effect, and the Stability of Farmers’ Poverty Alleviation in Deep Poverty Areas: A Case Study of S-County in Qinba Mountain Area

Abstract: Health status and income level are both important factors in reducing poverty and accomplishing sustainable development in deep poverty areas of China. Therefore, the purpose of this study is to provide policy support for the sustainable poverty alleviation of farmers by analyzing the net effect of health risk on Farmers’ income poverty and its impact mechanism. Based on the data of more than 199,000 farmers, this study uses the Difference in Difference (DID) model to empirically analyze the effect of health-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Remarkably, China achieved the United Nations' 2030 Agenda for Sustainable Development's poverty reduction goal a decade early, historically eradicating absolute poverty and creating an unprecedented feat in human poverty reduction history (Table 1). 2 The positive correlation between health risks and household poverty has been discussed in several studies (1)(2)(3). Using household survey data from China, Song et al (3) and Ma et al (4) found that health risks are a direct factor leading to poverty vulnerability in households.…”
Section: Open Access Edited Bymentioning
confidence: 98%
See 1 more Smart Citation
“…Remarkably, China achieved the United Nations' 2030 Agenda for Sustainable Development's poverty reduction goal a decade early, historically eradicating absolute poverty and creating an unprecedented feat in human poverty reduction history (Table 1). 2 The positive correlation between health risks and household poverty has been discussed in several studies (1)(2)(3). Using household survey data from China, Song et al (3) and Ma et al (4) found that health risks are a direct factor leading to poverty vulnerability in households.…”
Section: Open Access Edited Bymentioning
confidence: 98%
“…The positive correlation between health risks and household poverty has been discussed in several studies ( 1–3 ). Using household survey data from China, Song et al ( 3 ) and Ma et al ( 4 ) found that health risks are a direct factor leading to poverty vulnerability in households. Liao et al ( 1 ) discovered that under the impact of health risks, increased household medical expenses lead to reductions in total household capital, total labor, and per capita capital, ultimately plunging households into poverty.…”
Section: Introductionmentioning
confidence: 99%
“…Higher education has become the engine of social, economic, and human capital development [ 8 ]. The contribution of human capital to economic development has become a significant factor in promoting actual sustainable development [ 9 ]. By the end of 2021, China’s population of over six-year-olds was 14,411 million, of which 99.96% had reached the primary education level (See., Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%